N2O and CH4 fluxes in undisturbed and burned holm oak, scots pine and pyrenean oak forests in central Spain - Inclán, Rosa; Uribe, Carla; Sánchez, Laura; Sánchez, Dolores M.; Clavero, Ángeles; Fernández, Ana María; Morante, Ramón; Blanco, Alfredo; Jandl, Robert (Biogeochemistry, 2010)
We investigated N2O and CH4 ﬂuxes from soils of Quercus ilex, Quercus pyrenaica and Pinus sylvestris stands located in the surrounding area of Madrid (Spain). The ﬂuxes were measured for 18 months from both mature stands and post ﬁre stands using the static chamber technique. Simultaneously with gas ﬂuxes, soil temperature, soil water content, soil C and soil N were measured in the stands. Nitrous oxide ﬂuxes ranged from -11.43 to 8.34 lg N2O–N m -2 h -1 in Q.ilex, -7.74 to 13.52 lg N2O–N m -2 h -1 in Q. pyrenaica and -28.17 to 21.89 lg N2O–N m -2 h -1 in P. sylvestris. Fluxes of CH4 ranged from -8.12 to 4.11 lg CH4– C m -2 h -1 in Q.ilex, -7.74 to 3.0 lg CH4 –C m -2 h -1 in Q. pyrenaica and -24.46 to 6.07 lg CH4–C m -2 h -1 in P. sylvestris. Seasonal differences were detected; N2O ﬂuxes being higher in wet months whereas N2O ﬂuxes declined in dry months. Net consumption of N2O was related to low N availability, high soil C contents, high soil temperatures and low moisture content. Fire decreased N2O ﬂuxes in spring. N2O emissions were closely correlated with previous day’s rainfall and soil moisture. Our ecosystems generally were a sink for methane in the dry season and a source of CH4 during wet months. The available water in the soil inﬂuenced the observed seasonal trend. The burned sites showed higher CH4 oxidation rates in Q. ilex, and lower rates in P. sylvestris. Overall, the data suggest that ﬁre alters both N2O and CH4 ﬂuxes. However, the magnitude of such variation depends on the site, soil characteristics and seasonal climatic conditions.
Keywords: á; fire; greenhouse flux á fire; Greenhouse ﬂux; Pinus sylvestris; Quercus ilex; Quercus pyrenaica; quercus pyrenaica á pinus; Soil temperature; soil temperature á; Soil water content; soil water content á; sylvestris á